Assessment of infant mortality surveillance: case study - Conceição Maria de Oliveira; Paulo Germano de Frias; Cristine Vieira do Bonfim; Verônica Cristina Sposito Antonino; Joana D'arc Tavares do Nascimento; Zulma Maria Medeiros
Abstract Objectives: assess the implementation of child mortality surveillance in Recife/PE. Methods: an analytical evaluative study was conducted on its implementation. It was a single-case study that correlated degree of implementation with the of the result indicators surveillance. A logic model on this strategy and a matrix of indicators and judgments according to model components were drawn up. The degree of implementation was obtained from structure and process indicators and this was then correlated with result indicators, in a deductive approach based on intervention theory. Results: the structure approach presented superior results to the process in all evaluated components. This strategy was considered to have been partially implemented (75. 7%), however, the components of 'identification of deaths' (85.7%), 'epidemiological research' (88.1%) and 'referral of proposals for promotion and health care and correction of official statistics' (95.8%) were classified implemented. Regarding the relation of the degree of implantation of the surveillance and its results with the logical model, only one of the 17 indicators was considered inconsistent. Conclusions: this strategy was considered to have been partially implemented. The model of child mortality surveillance and its assessment were shown to be adequate for signaling the consistency of the interrelations between the activities proposed and the effects expected, and would be reproducible within other scenarios.